Genetic Variations in Nucleotide Excision Repair Pathway Genes and Risk of Allergic Rhinitis - Liu, Wenlong; Zeng, Qingxiang; Zeng, Yinhui; Tang, Yiquan; Luo, Renzhong (Mediators of Inflammation, 2022)
Background. Allergic rhinitis (AR) is the most frequent inflammatory disorder in the nasal mucosa that remains unclear etiology. Mounting studies suggested that genetic instability could trigger and worsen the inflammatory response. The nucleotide excision repair (NER) system is an important pathway in maintaining the stability of the genome. Therefore, the genetic variations in NER pathway genes may have potential effects on AR risk. Methods. We evaluated the correlation between 19 candidate single nucleotide polymorphisms (SNPs) in NER pathway genes and AR susceptibility by a case-control study in a Chinese population, which contains 508 AR cases and 526 controls. Results. Three independent SNPs were identified as significantly associated with AR susceptibility, including ERCC1 rs2298881 C>A (recessive model: adjusted odds ratios OR=0.30, 95%confidence interval CI=0.18–0.50, P<0.0001), ERCC1 rs11615 G>A (dominant model: adjusted OR=1.44, 95%CI=1.04–2.01, P=0.030), and XPC rs2228001 A>C (dominant model: adjusted OR=0.68, 95%CI=0.49–0.95, P=0.024). Stratified analysis showed that ERCC1 rs2298881 AA genotype was correlated with a lower risk of AR among all the subgroups compared with rs2298881 CC/CA genotype. XPC rs2228001 AC/CC genotype reduced AR risk among the following subgroups: age>60 months, clinical stage I and III. Conclusion. Our finding showed that genetic variations in NER pathway genes: ERCC1 and XPC may affect the risk of AR, which will provide new insights into the genetics of AR from the perspective of DNA damage repair.